Social Capital and Community Building in Rural Ontario Libraries - Johnson, Catherine A.; Griffis, Matthew R. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This presentation reports on a study that investigated the relationship between public libraries and social capital in rural communities in Ontario. Preliminary findings suggest that, in contrast to urban communities, the use of libraries in small towns is not significantly related to increases in levels of social capital. Cette communication présente une étude portant sur la relation entre les bibliothèques publiques et le capital social dans les régions rurales de l'Ontario. Les résultats préliminaires suggèrent que contrairement en milieux urbains, l'utilisation de bibliothèques en milieu rural n'est pas intimement lié à un accroissement du capital social.